Magnetophotonic crystal on base of gyrotropic semiconductor and metamaterial - Odarenko, E. N.; Shmat'ko, A. A.; Mizernik, V. N.; Maslov, V. A. (Lesya Ukrainka Volyn National University, 2018)
One-dimensional magnetophotonic crystal which contains semiconductor and metamaterial layers is considered. Dispersion properties are investigated within the framework of ABCD matrix method for gyrotropic periodical structures. Surface waves exist conditions are considered for different system parameters. Possibility of narrow-band filters development is shown on the base of multilayered structure under investigation.
Keywords: magnetophotonic crystal; dispersion equation; gyrotropy; semiconductor; metamaterial